2015
DOI: 10.1002/joc.4332
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime climate factors controlling snow resource decline in Finland

Abstract: Numerous studies have reported significant declines in snow resources in Finland and elsewhere during the 20th century. To identify the main climate factors controlling these declines in Finland, this study evaluated long‐term variations and trends in wintertime climate, snowpack hydrological processes (SHPs) and continuous snow cover duration (CSCD), and their links to atmospheric circulation patterns (ACPs). Analyses were conducted using observed daily climatological time series and simulated SHPs at three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 99 publications
(161 reference statements)
2
29
0
1
Order By: Relevance
“…An option is also to apply a snowpack model to simulate SWE, as undertaken by Irannezhad et al . () for three stations in Finland. They found that during a recent century‐long period, the simulated annual peak SWE decreased and shifted in time to earlier dates and the continuous snow cover duration shortened at three weather stations located in southern, central and northern parts of the country.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…An option is also to apply a snowpack model to simulate SWE, as undertaken by Irannezhad et al . () for three stations in Finland. They found that during a recent century‐long period, the simulated annual peak SWE decreased and shifted in time to earlier dates and the continuous snow cover duration shortened at three weather stations located in southern, central and northern parts of the country.…”
Section: Discussionsupporting
confidence: 63%
“…Some datasets of SWE do exist, such as the SYKE snow survey data (Reuna, 1994) and the GlobSnow SWE product (Luojus et al, 2013), but they typically cover a shorter time range or are of coarser temporal or spatial resolution than the FMIClimGrid dataset utilized in this paper. An option is also to apply a snowpack model to simulate SWE, as undertaken by Irannezhad et al (2016) for three stations in Finland. They found that during a recent centurylong period, the simulated annual peak SWE decreased and shifted in time to earlier dates and the continuous snow cover duration shortened at three weather stations located in southern, central and northern parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…A number of long-term continuous climatic monitoring series are available in the NAR (e.g., Kohler et al 2006;Nordli et al 2014), comprising a unique record for studies related to Arctic climate change and variability during winter. The region is a primary pathway for the transport of atmospheric energy into the Arctic (Serreze et al 2007) and is situated in a projected hot spot area with increased heat fluxes from the Atlantic water masses (e.g., Årthun et al 2012), the retreat of winter sea ice (Onarheim et al 2014), and a decrease in snow cover (e.g., Irannezhad et al 2015). These processes are connected with a relatively large transition to more frequent temperatures above 08C (e.g., Førland et al 2011) and an increase in precipitation (e.g., Fleig et al 2015) and heavy rainfalls during winter (e.g., Hansen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It affects spring floods, low flows in early summer, groundwater recharge and soil moisture conditions (Kinar and Pomeroy, 2015;Okkonen and Kløve, 2011). Recent climate projections (IPCC, 2014) and studies (Irannezhad et al, 2016;Räisänen and Eklund, 2012;Sturm et al, 2009) indicate drastic future changes in snow cover properties and the timing of snowmelt in boreal and arctic regions. Precipitation in circumpolar areas is projected to increase (IPCC, 2014), but snowfall is indicated to decrease (Irannezhad…”
Section: Introductionmentioning
confidence: 99%